Rezension von: Bradlow, Frank Rosslyn, Baron von Ludwig and the Ludwig's-burg Garden - Vietzen, Hermann (Schwäbische Heimat, 1965)
Trank R. Bradlow: Baron von Ludwig and the Ludwig' s-Burg Qarden. A chronide of the Cape from 1806 to 1848. A. A. Baldema. Cape Town/Amsterdam, 1965